The new employment contract - Kissler, Gary D. (Human Resource Management, 1994)
AbstractFrom the turmoil of the last decade a new relationship has emerged between employees and their organizations. It is one that openly challenges many of the management assumptions behind the imbalance of power between the key participants. Making a successful adjustment to this change has enormous implications in terms of sustained competitive advantage based on the ability to access and retain a committed and skilled work force. Human Resource professionals will find themselves caught in competing loyalties as their roles in this change process evolve. This article offers insight into this changing contract and its impact on the business environment.